Predation increases acoustic complexity in primate alarm calls - Stephan, Claudia; Zuberbühler, Klaus (Biology Letters, 2008)
According to most accounts, alarm calling in non-human primates is a biologically hardwired behaviour with signallers having little control over the acoustic structure of their calls. In this study, we compared the alarm calling behaviour of two adjacent populations of Diana monkeys at Taï forest (Ivory Coast) and Tiwai Island (Sierra Leone), which differ significantly in predation pressure. At Taï, monkeys regularly interact with two major predators, crowned eagles and leopards, while at Tiwai, monkeys are only hunted by crowned eagles. We monitored the alarm call responses of adult male Diana monkeys to acoustic predator models. We found no site-specific differences in the types of calls given to eagles, leopards and general disturbances, but there were consistent differences in how callers assembled calls into sequences. At Tiwai, males responded to leopards and general disturbances in the same way, while at Taï, males discriminated by giving call sequences that differed in the number of component calls. Responses to eagles were identical at both sites. We concluded that Diana monkeys are predisposed to use their repertoire in context-specific ways, but that ontogenetic experience determines how individual calls are assembled into meaningful sequences.<br
Keywords: predation; compositionality; vocal learning; evolution of language